2022
DOI: 10.3390/v14020267
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus Infections among Hematopoietic Stem Cell Transplant Recipients: A Pre-Transplant Dilemma?

Abstract: Respiratory viral infections (RVIs) in allogeneic hematopoietic stem cell transplant (allo-HSCT) recipients can be of concern due to the patients’ depressed immune status, but few data are available about the significance of a pre-transplant positive testing. In this retrospective observational study, we analyzed a cohort of patients that were transplanted between 1 January 2010 and 31 October 2019 in the Geneva University Hospitals with at least one RVI before or after transplantation. At least one RVI was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 18 publications
3
15
1
Order By: Relevance
“…The prevalence of human polyomavirus infection is very high in the adult populations [5,17 ▪ ]. Apart from the well known pathogenic BK polyomavirus regularly screened for in allogeneic HCT recipients, recent studies identified the frequent presence of JC polyomavirus (JCPyV) as well as several novel polyomaviruses in plasma, such as Merkel cell polyomavirus (MCPyV), HPyV6 and HPyV7, albeit of unclear clinical significance for the time being [5,17 ▪ ]. In rare cases, JCPyV reactivation causes progressive multifocal leukoencephalopathy in the immunocompromised host; however, in the vast majority of allogeneic HCT patients, JCPyV reactivation has not yet been linked to any clinical manifestation or impact on HCT outcome [31].…”
Section: The Impact Of Highly Prevalent Viruses On Hematopoeitic Cell...mentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of human polyomavirus infection is very high in the adult populations [5,17 ▪ ]. Apart from the well known pathogenic BK polyomavirus regularly screened for in allogeneic HCT recipients, recent studies identified the frequent presence of JC polyomavirus (JCPyV) as well as several novel polyomaviruses in plasma, such as Merkel cell polyomavirus (MCPyV), HPyV6 and HPyV7, albeit of unclear clinical significance for the time being [5,17 ▪ ]. In rare cases, JCPyV reactivation causes progressive multifocal leukoencephalopathy in the immunocompromised host; however, in the vast majority of allogeneic HCT patients, JCPyV reactivation has not yet been linked to any clinical manifestation or impact on HCT outcome [31].…”
Section: The Impact Of Highly Prevalent Viruses On Hematopoeitic Cell...mentioning
confidence: 99%
“…With the emergence of the virome concept, several studies have been performed by the Geneva group in the last years to better describe the blood virome among allogeneic HCT patients [15,16 ▪ ,17 ▪ ,18 ▪▪ ,19 ▪ ] (Table 1). In a study by Vu et al [15], mNGS was used on plasma samples of 40 patients to provide a description of the blood virome at 1-month post-HCT.…”
Section: The Composition Of the Human Blood Virome In Allogeneic Hema...mentioning
confidence: 99%
See 1 more Smart Citation
“…15 A recent study found no direct association between pretransplant RVI and mortality in adult HCT patients. 16 Using meta-transcriptomic sequencing of pre-HCT bronchoalveolar lavage (BAL) samples, a third study identified distinct signatures of viral infection and commensal bacterial depletion that were associated with significantly increased post-HCT lung injury and fatal lung injury. 17 To date, studies have been limited by small size, precluding multivariable statistical analysis of factors associated with outcome such as location of infection or conditioning regimen.…”
Section: Introductionmentioning
confidence: 99%
“…In order to better understand the dynamics of nosocomial spread and clinical manifestations of HPIV-3 infections we retrospectively reviewed the results of all respiratory panel PCR tests from nasopharyngeal swabs performed on 883 patients at our hospital in an 8-month period (November 2016 to June 2017) surrounding the outbreak. We compared clinical manifestations and outcomes of patients infected with HPIV-3 (cases) and patients (controls) infected with rhino-/enteroviruses, which are the most frequent cause of respiratory virus infections in both immunocompetent and immunocompromised individuals [ 4 ]. Cases and controls were matched for age, gender, immunosuppressive treatment and HCT.…”
mentioning
confidence: 99%